Thin-layer drying kinetics of nectarine slices using IR, MW and hybrid methods - Ismail, O.; Kipcak, A. S.; Doymaz, I.; Piskin, S. (BULGARIAN ACAD SCIENCE, 2017)
In this study, slices of nectarines (var. nucipersica or var. nectarine maxim) were dried using three different drying methods: microwave (MW), infrared (IR) and hybrid (combined IR and MW). MW drying method was applied with power levels between 90-600 W, while IR drying method was applied with a power level of 125 W. For the hybrid drying, 125 W of IR and 180 W of MW were consecutively applied. Along with the aforementioned methods a pre-treatment process with citric acid was also applied. Minimum drying time of 127 min was reached using the hybrid drying method. After obtaining the experimental drying values, drying kinetics was calculated using mathematical modeling by different methods widely used in the literature. Considering the high coefficient of determination (R-2), low root mean square error (RMSE) and low chi-square (chi(2)) values, the Aghbashlo et al. model was found to be the best one.
Keywords: MW drying; IR drying; hybrid drying; Aghbashlo et al. model; INFRARED RADIATION; MICROWAVE; QUALITY; APPLE; COLOR; DEHYDRATION; VACUUM; TOMATO; MODELS; CARROT; Chemistry